Influence of Glenn Doman Method toward Start Reading Skills Moderately Retarded Children Increase in Tut Wuri Handayani Special School - Wulandari, Fransisca Diyan Inge; Aprilia, Imas Diana; Susetyo, Budi; Muchlisah, Anugerah (Proceeding of International Conference on Special Education in South East Asia Region, 2022)
Moderately retarded children have a problem with reading the start, especially in remembering form letter, mixing syllables into word, distinguishing sound, and understanding reading. In general, learning to read in special school is more emphasis on recitation the alphabet that will be repeated until the children can be remember the alphabet. Therefore, learning becomes monotonous and boring. For upgraded reading skills, then it’s need method that not emphasize children in learning, that is Glenn Doman method. Glenn Doman method is use to upgrading reading skills, because this method just stimulates children brain to develop without burdening children to read per syllable, but just seeing the word and listen the spell word. Moreover, this method was applied by playing so as make children more relax in studying. Generally, this research is aim for knowing the influence of usage Glenn Doman method to reading skills with the start moderately retarded children in 6th grade. The method that used is experiment method with types of SSR (single subject research).